PENERAPAN MODEL WATERFALL PADA APLIKASI PENJUALAN ONLINE KOPERASI RANCAGE KAMPUNG KALENG BOGOR - Fitria Ramdani; Laila Septiana (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
Indonesian e-commerce transactions are the highest in Southeast Asia. one of them is a type of business that must maximize the use of the internet, namely small and medium micro businesses. in Bogor district, the place where the village of RT 003/01 is located in the Pasir Mukti village of Citeruep sub-district, where the surrounding community groups to make handicrafts from aluminum in a cooperative called Rancage business cooperative. the main problem faced by micro, small and medium enterprises is marketing, marketing with conventional methods requires high costs. the development of the internet has become an efficient means of opening new marketing channels for micro, small and medium enterprises. in addition to the relatively low cost, utilizing the internet information dissemination will be faster and broader in scope. so that online or e-commerce buying and selling transactions make it easier to reach the public. the author observes and interviews the chairman of the all-business cooperative rancage whose sales are still using conventional methods.